Microbial nanomaterials: Role in sustainable agricultural practices - MUKHERJEE, SHAON; SIDDIQUI, JAMAL; SAXENA, JUHI (The Indian Journal of Agricultural Sciences, 2024)
The increased use of chemical fertilizers, pesticides, soil-based heavy metals to improve productivity in agriculture results into higher pollution level in agroecosystem. It has become a major issue on a global scale that seriously jeopardizes people’s health and welfare as well as affects society and overall economy. In view of this, there is an urgent need to detect pollutants in the agroecosystem so that remediation practices can be implemented in time. The evolution of more responsive, affordable and precise technology is needed to create nano-sensors or nanodevices that can be used to monitor agricultural pollution, and the processes involved in pollution control. Major focused ones are those that can detect pollutants at very low concentration levels, as well as point-to-point sensing, in situ, and uninterrupted monitoring devices that offer synchronized data. These sensors are readily available in the market for the detection of organic pollutants, gases, volatile organic molecules, heavy metal ions, hazardous metal ions, etc. but they consume a lot of power and lack sophisticated technologies for improved selectivity and sensitivity. Their precision, sensitivity, response speed and environmental stability under actual operating conditions can all be improved with the aid of nanotechnology. In this study an attempt was made to describe how microbial biosensors can be used to detect toxic materials in agroecosystems. Additionally, an application of nanomaterials as pesticides and antimicrobial agent has also been discussed.